OPTIMIZATION OF SUPPLIES OF MATERIAL RESOURCES IN THE LOGISTICS SYSTEM THE CONSTRUCTION OF ROADS - I. M. Tsarenkova (Наука и техника)
Logistics plays a significant role in resource provision of automobile road construction. The following specific factors have rather high influential character, namely: necessity to use various types of material resources, presence of multicomponent semi-finished products that require final preparation on the construction site, rather large linear length of objects that requires formation of logistics road-construction flow, distance from production bases of construction organizations, dependence of production on natural and climatic factors, distinct seasonality of executed works. All these conditions influence on specific organizational and economic forms of logistics processes while constructing automobile roads. In order to apply a logistics approach for organization of the automobile road construction it is expedient to make modeling of systems for supply of material resources to ensure continuous process of works. Such approach will permit to specify processes requiring optimization. The proposed logistics approach to rational organization of supply for material resources required for automobile road construction presupposes control of all operations which must be carried out on the path of material flow motion. Specific feature of supply chain of material resources in the logistics system for automobile road construction is a direct dependence of final product quality on technology compliance during execution of works which is directly connected with timely supply of materials. Optimization is achieved through selection of quantitative composition of transport facilities, improvement of their productivity and selection of rational transportation schemes using a criterion of minimum cost. Usage of mathematical apparatus allows to calculate optimal number of transport facilities in the logistics system for automobile road construction, ensuring smooth delivery of material resources to the object with due account of the required rate of construction works.